Prevalence of Nasal Colonization by Methicillin-Resistant Staphylococcus aureus in Persons Using a Homeless Shelter in Kansas City - Ottomeyer, Megan; Graham, Charles D.; Legg, Avery D.; Cooper, Elizabeth S.; Law, Chad D.; Molani, Mariam; Matevossian, Karine; Marlin, Jerry; Williams, Charlott; Newman, Ramon; Wasserman, Jason A.; Segars, Larry W.; et al. (Frontiers in Public Health, 2016)
Nasal colonization of methicillin-resistant Staphylococcus aureus (MRSA) plays an important role in the epidemiology and pathogenesis of disease. Situations of close-quarter contact in groups are generally regarded as a risk factor for community acquired MRSA strains due to transmission via fomites and person to person contact. With these criteria for risk, homeless individuals using shelter facilities, including showers and toilets, should be considered high risk for colonization and infection. The aim of this study was to determine the prevalence of nasal colonization of MRSA in a homeless population compared to established rates of colonization within the public and a control group of subjects from a neighboring medical school campus, and to analyze phylogenetic diversity among the MRSA strains. Nasal samples were taken from the study population of 332 adult participants, and analyzed. In addition, participants were surveyed about various lifestyle factors in order to elucidate potential patterns of behavior associated with MRSA colonization. Homeless and control groups both had higher prevalence of MRSA (9.8% and 10.6% respectively) when compared to the general population reported by previous studies (1.8%). However, the control group had a similar MRSA rate compared to healthcare workers (4.6%) while the homeless population had an increased prevalence. Risk factors identified in this study included male gender, age over 50 years and use of antibiotics within the past 3 months. Phylogenetic relationships between 9 of the positive samples from the homeless population were analyzed, showing 8 of the 9 samples had a high degree of relatedness between the spaA genes of the MRSA strains. This indicates that the same MRSA strain might be transmitted from person to person among homeless population. These findings increase our understanding of key differences in MRSA characteristics within homeless populations as well as risks for MRSA associated with being homeless, such as age and gender, which may then be a useful tool in guiding more effective prevention, treatment, and healthcare for homeless individuals.